Killer Acquisitions no setor financeiro brasileiro: uma análise antitruste dos casos Ágora-Bradesco e XP-Itaú - Abreu, Luiz Felipe Bittencourt de (2023)
The present study aimed to address Killer Acquisitions in the Brazilian financial sector by analyzing the cases of Ágora-Bradesco and XP-Itaú in the context of antitrust scrutiny and challenges posed by digital markets. Killer Acquisitions refer to a strategy where a company acquires a promising competitor with the intention of preventing it from growing into a significant threat in the future. Digital markets have introduced unique challenges to antitrust scrutiny due to rapid innovation and technological evolution, making it difficult to define competition boundaries. Financial technology companies (fintechs) and startups have gained traction in the financial sector, providing innovative and disruptive services. Killer Acquisitions can be a strategy employed by major financial institutions to eliminate potential competitors and maintain their dominant position in the digital market. The study seeks to evaluate concentration acts through the lens of the theory of harm of Killer Acquisitions in digital markets and their possible consequences after the operations. The conducted study highlights that in the specific cases of ÁgoraBradesco and XP-Itaú, the firms in question are not nascent entities, but rather established companies with disruptive profiles that have brought about significant changes in their operating markets, resembling Maverick firms. In the case of Ágora, reconsideration of the treatment of relevant markets could be warranted, especially given Ágora's leading position in a rapidly growing segment where individuals execute operations via Home Broker. In the subsequent XP case, occurring nearly a decade later, distinct actions were taken by antitrust authorities, both by CADE and, in this instance within the financial sector, by the Central Bank. The implementation of behavioral remedies, limiting Itaú's interference, preserved XP's competitiveness and may have enabled it to sustain its disruptive business model without reducing competitive pressure on the incumbents.